Social and Psychological Features of Crime Groupings - Gabdulbarovna Mukhametzyanova, Flera (2020)
The article reveals the potential of implementation of different theories in the process of creation of the complex methodology of the research of social and pedagogical features of the members of teenager-youth street crime groupings (gangs). The author creates the design of indicative model allowing to notice the condition of social and adaptive potential of the personality of teenage youth: motivation for behavior and actions, reflexive abilities, value- meaning sphere and the level of the behaviour aggression. The author concludes that there is a necessity to determine subjective potential of the teenage youth personality, who are the members of gangs for designing the system of preventive measures against involvement them in the gangs and further successful social adaptation and socialization after quitting the gang.  The author concludes that the obtained data can be the basis for the development of preventive measures in the process of working with the teenagers from the risk group.